2022
DOI: 10.1002/jor.25256
|View full text |Cite
|
Sign up to set email alerts
|

Use of portable ultrasonography for the diagnosis of lateral ankle instability

Abstract: Portable ultrasonography is increasingly used to evaluate ankle stability at the point of care. This study aims to determine the correlation of portable‐ultrasonographic and fluoroscopic measurements of ankle laxity in a cadaveric ligament transection model of ankle ligament injury. We hypothesize that there is an association between portable‐ultrasonographic and fluoroscopic measurements when performing stress evaluation of lateral ankle instability. Eight fresh‐frozen below‐knee amputated cadaveric specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Stress ultrasonography (US) has been reported to be a reliable and useful tool for evaluating lateral ankle laxity [10,11]. It has been reported that the anterior talofibular ligament (ATFL) ratio, which is defined as a ratio of stress ATFL length to non-stress ATFL length, is a useful parameter to assess lateral ankle laxity by stress US [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Stress ultrasonography (US) has been reported to be a reliable and useful tool for evaluating lateral ankle laxity [10,11]. It has been reported that the anterior talofibular ligament (ATFL) ratio, which is defined as a ratio of stress ATFL length to non-stress ATFL length, is a useful parameter to assess lateral ankle laxity by stress US [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…All fluoroscopic images were obtained using a technique previously described by Saengsin et al 30 Two standardized loading conditions were created: (1) an anterior drawer test with 50 and 80 N of direct force to quantify anterior talar translation relative to the tibia (Figure 1) 30 and (2) a talar tilt test under 1.7 Nm of torque to measure the talar tilt angle and lateral clear space (the distance between the lateral talar process and tip of the fibula) (Figure 2). 30 Prior studies have highlighted that 30 to 60 N of force is sufficient when performing the anterior drawer test to evaluate ATFL injury; thus, a force of 50 N was used to measure anterior talar translation. 22,35,36 Similarly, prior cadaveric studies have reported the ultimate load to failure of an uninjured ATFL or CFL as ranging from 90 to 307 N 2,33,38 ; thus, a force of 80 N was used as the maximum amount of physiologic load to prevent plastic deformation or rupture.…”
Section: Methodsmentioning
confidence: 99%
“…In both loaded and unloaded states, the anterior talar translation, or the distance between the tibial axis and the center of the talus on lateral radiographs, was determined, and the difference in anterior talar translation between both loading states was calculated (Figure 1). 30 Similarly, in both loaded and unloaded states, the lateral clear space distance and the talar tilt angle were determined on the AP radiographs, and the difference in the lateral clear space distances and the talar tilt angles between both loading states was calculated (Figure 2). 30…”
Section: Fluoroscopic Assessmentmentioning
confidence: 99%
See 2 more Smart Citations